Epidemiological Dynamics of HIV Infection and the Proportion of Injection Drug Users in the Republic of Uzbekistan during 2020–2022 and Their Impact on the Psychology of Patients Living with HIV/AIDS (Eurasian Journal of Learning and Academic Teaching, 2026)
This study analyzed the epidemiological dynamics of HIV infection in the Republic of Uzbekistan during 2020–2022 and the first six months of 2023, the proportion of people who inject drugs (PWID), and the impact of these changes on the psychology of patients living with HIV/AIDS. Retrospective statistical analysis methods were applied. The results showed that from 2020 to 2022, the overall incidence of HIV infection increased by 38%, while the proportion of PWID decreased from 3.0% to 2.1%, reaching 1.35% in the first half of 2023. Changes in the epidemiological structure significantly affect stigma, anxiety, and processes of social adaptation. The study demonstrates the necessity of an integrative epidemiological and psychological approach